Test-retest and inter-rater reliabilities of the of Manual Ability Classification System (MACS) - Farsi version in children with cerebral palsy - Azade Riyahi; Mehdi Rassafiani; Nazila Akbarfahimi; Masood Karimloo (Vesnu Publications, 2012)
Introduction: Assessing the abilities of children with cerebral palsy has an important role in planning intervention and providing services by relevant organizations such as Iran's Welfare Organization. Through classifying hand functions, the Manual Ability Classification System (MACS) helps to achieve this goal. MACS has been recently translated into Farsi but further studies need to be carried out regarding its reliability. Therefore, this study aimed at determining the test-retest and inter-rater reliabilities of the Farsi version of the MACS in children with cerebral palsy (CP). Materials and Methods: For investigating the reliability of the Persian version of the MACS, inter-rater and test-retest reliability was assessed by comparing ratings of 6 occupational therapists who measured videotaped hand functions of 39 cerebral-palsied Children (23 boys, 16 girls; age range: 4-18 years, mean: 93.12 months) during daily activities.  Participants were affected by various types of CP. The intra-class correlation coefficient (ICC) and the weighted kappa coefficient were used for statistical analysis of data using SPSS version 16. Significance level was set at P ≤ 0.05. Results: Findings indicated high inter-rater reliability between 6 occupational therapists so that the first- and the second-round ICC values respectively were 0.96 and 0.95. Weighted kappa coefficient was higher than 0.75, again revealing excellent agreement. With regard to test-retest reliability, the ICC values for occupational therapists were found to be 0.98 and weighted kappa coefficient was 0.75 which showed excellent agreement between raters' measurements. Conclusion: The Persian version of the MACS has a high test-retest and inter-rater reliability and is seemed to be appropriate for assessing the manual ability of Iranian children with CP Keywords: Assessment tool, Cerebral palsy, Reliability, Manual ability classiﬁcation system